Decline of Executive Processes Affects the Identification of Emotional Facial Expressions in Aging - Garcia-Rodriguez, Beatriz; Fusari, Anna; Fernandez-Guinea, Sara; Frank, Ana; Antonio Molina, Jose; Ellgring, Heiner (Current Aging Science, 2011)
The current study examined the hypothesis that old people have a selective deficit in the identification of emotional facial expressions (EFEs) when the task conditions require the mechanism of the central executive. We have used a Dual Task (DT) paradigm to assess the role of visuo-spatial interference of working memory when processing emotional faces under two conditions: DT at encoding and DT at retrieval. Previous studies have revealed a loss of the ability to identify specific emotional facial expressions (EFEs) in old age. This has been consistently associated with a decline of the ability to coordinate the performance of two tasks concurrently. Working memory is usually tested using DT paradigms. Regarding to aging, there is evidence that with DT performance during encoding the costs are substantial. In contrast, the introduction of a secondary task after the primary task (i.e. at retrieval), had less detrimental effects on primary task performance in either younger or older adults. Our results demonstrate that aging is associated with higher DT costs when EFEs are identified concurrently with a visuo-spatial task. In contrast, there was not a significant age-related decline when the two tasks were presented sequentially. This suggests a deficit of the central executive rather than visuo-spatial memory deficits. The current data provide further support for the hypothesis that emotional processing is “top-down” controlled, and suggest that the deficits in emotional processing of old people depend, above all, on specific cognitive impairment.
Keywords: neurological aging